PENDAPATAN DAN KESEJAHTERAAN PETANI KARET RAKYAT DI KECAMATAN BUMI AGUNG KABUPATEN WAY KANAN - Reny Mardiana; Zainal Abidin; Achdiansyah Soelaiman (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2014)
This research aimed at analyzing family income of small-scale rubber plantation product, family welfare of small-scale rubber plantation product in Bumi Agung Subdistrict, Way Kanan District.  The number of respondents were 51 people using simple random sampling. The method used was survey method with the technique of the interview (questionnaire). The data was extracted from the primary and secondary data.  The study used the quantitative descriptive analysis with tabulation and computerization.  The study to analizing of family income, poverty level by Sajogyo (1997), and family welfare by BPS (2009).   The results showed the average income for a family was Rp13,245,069.59 per ha per year.  Based on Sajogyo criteria, family was live well as many as 45 family and based on BPS criteria as many as 43 family walfare from 51 of small-scale rubber plantation product. Keywords : income analysis, poverty, small-scale rubber plantation product, welfare